Kuala Langsa People's Behavior Towards Environmental Conservation is Reviewed from the Aspect of Social Change - Tutdin, Zakiya; Syah, Elisa Putri (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
Located the in this area there are a number of tourist destinations, such as mangrove forests, green bridges, mangrove forest monitoring towers that are crowded with visitors on weekends, and a port that has existed since before the colonial period. As a dynasty tourism area, it certainly opens up economic opportunities for the local community. The purpose of this study is to determine the behavior of Kuala Langsa's local community activities toward environmental preservation in terms of social change. This research was conducted using a descriptive qualitative method. The results of the study are seen from the aspect of social change that occurs in the local community of Kuala Langsa. Factors that influence social change are internal and external. Internally includes the desire and awareness, as well as human decisions to be able to change, so it is necessary to change the mindset of the community. External changes include changes in regulations from agencies or governments related to regulations to preserve the environment, and the habits of tourists who come from outside. So, a shared awareness is needed for better social change such as protecting the environment and not allowing the environment to be exploited